A noninvasive method for the detection of foetal DNA in early pregnancy based on differential methylation pattern of Ras association domain family member 1A - Yulin Sha; Wei Liu; Jiongzhi Hong; Yan Yang; Jian Yu; Xiaodong Fu (Journal of Obstetrics and Gynaecology)
Background The detection of foetal DNA and extravillus trophoblasts (EVTs) in early pregnancy in cervical and uterine samples offers a potential pathway for non-invasive prenatal diagnostics. However, the challenge lies in effectively quantifying these samples. This study introduces a novel approach using the Ras association domain family 1 A (RASSF1A), which exhibits hypermethylation in foetal cells and hypomethylation in maternal cells. The differential methylation pattern of RASSF1A provides a unique biomarker for quantifying foetal cells in cervical and intrauterine samples.Methods This study was conducted between September 2022 and May 2023. In total, 23 samples (12 cervical cell samples and 11 intrauterine samples) were collected from women in the Sichuan Jinxin Women & Children Hospital, Jingxiu District, Chengdu, China. The cervical cell samples were collected via lavage and brush techniques, and the intrauterine cell samples were obtained via uterine lavage. These samples were collected as part of a broader effort to advance our understanding of foetal cell dynamics during early pregnancy. The sampling methods were chosen for their minimally invasive nature and their potential in capturing a representative cell population from the respective sites. After digestion of the cell samples using a methylation-sensitive restriction enzyme cocktail, a critical step to differentiate between maternal and foetal DNA, the quantitative polymerase chain reaction (qPCR) of RASSF1A and β-actin (ACTB) were employed to measure foetal DNA and cell concentrations. Immunofluorescence techniques targeting histocompatibility complex, class I G (HLA-G) and GATA binding protein 3 (GATA-3) were employed to detect EVTs in the cell samples and in decidual tissue, with the latter providing an additional layer of confirmation for the presence of foetal cells.Results The results showed no hypermethylated RASSF1A was detected in any of the cervical samples, irrespective of whether the samples were obtained by brush or lavage. However, an average of 17,236 ± 7490 foetal cells per sample were detected in the uterine lavage samples. Foetal cells accounted for approximately 0.14% ± 0.10% of the total cell population in these samples. The presence of EVTs in these samples was confirmed by their expression of both HLA-G and GATA-3.Conclusion The detection of foetal cells in uterine cavity samples based on hypermethylation of RASSF1A and quantification of foetal cells can be used to prenatal screening. GATA-3 can be used to label EVTs.